Relevansi Konsep Pendidikan Driyarkara dengan Pendidikan Karakter dalam Pembelajaran Sejarah - Linggar Charista Shary (HEURISTIK: Jurnal Pendidikan Sejarah, 2022)
The concept of Driyarkara education is an educational concept that cannot be separated from the process of hominization and humanization. The process is intended to become a human being who reaches the level of humanity through character education. Historical education contains various historical events whose moral messages can be taken as a form of inculcating character education in students. This study discusses the relevance between the concept of Driyarkara education and character education in historical education. This study uses qualitative methods and literature study to collect various sources related to this study. The purpose of writing this study is to determine the relevance between the concept of Driyarkara education and character education in historical education. The material content in history contains various moral values that can be taken and instilled in students, so that the process is a process of humanizing young people and the process of becoming human beings who reach the level of humanity through character education.